2013
DOI: 10.3109/13814788.2013.838670
|View full text |Cite
|
Sign up to set email alerts
|

Why do patients discontinue antidepressant therapy early? A qualitative study

Abstract: Health care professionals would benefit from exploring patient knowledge and views on depression and antidepressants at an early stage in treatment. Patients would welcome active involvement in treatment decision making, the provision of information and ongoing support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…It seems that the discontinuation could be due to rational patient behaviour balancing improved asthma control against adverse effects, price and convenience. This is in line with the finding of qualitative studies on other treatments, where ownership, knowledge and support were important factors for patient adherence .…”
Section: Discussionsupporting
confidence: 89%
“…It seems that the discontinuation could be due to rational patient behaviour balancing improved asthma control against adverse effects, price and convenience. This is in line with the finding of qualitative studies on other treatments, where ownership, knowledge and support were important factors for patient adherence .…”
Section: Discussionsupporting
confidence: 89%
“…Together these identify a new potential factor which may influence early antidepressant discontinuation, possibly linking with perceived inertia and service dissatisfaction as previously identified [48, 49]. Prescribers also demonstrated that antidepressants were only one of many treatment modalities, and that the GPs themselves had a therapeutic function as listener, counsellor and facilitator [4951], as well as creating space through use of sickness certificates [52].…”
Section: Discussionmentioning
confidence: 88%
“…Across the literature, stigma emerged as a concept of central importance to women engaged in treatment DM related to antidepressant use during pregnancy. The stigma of depression (Cooper-Patrick et al, 1997;Fosgerau & Davidsen, 2014;Garfield et al, 2004;Jaffray, Cardy, Reid, & Cameron, 2014;Kwintner, 2005;Malpass et al, 2009;Maxwell, 2005;Simon et al, 2007;Stecker & Alvidrez, 2007;van Geffen et al, 2011;Verbeek-Heida & Mathot, 2006) and the fear of dependency on antidepressants (Garfield et al, 2004;Jaffray et al, 2014;Johnston, 2013;Kwintner, 2005;Malpass et al, 2009;Maxwell, 2005;Simon et al, 2007;van Geffen et al, 2011;Verbeek-Heida & Mathot, 2006) are two of the most frequently identified barriers in the broader depression treatment DM literature. In the context of pregnancy, women have a heightened awareness of social norms and feel intense pressure to conform, even outside the context of depression (Baggley, Navioz, Maltepe, Koren, & Einarson, 2004;Lupton, 2011;Noseworthy et al, 2013;Santalahti, Hemminki, Latikka, & Ryynänen, 1998;Wittmann-Price & Bhattacharya, 2008…”
Section: Discussionmentioning
confidence: 99%